2016
DOI: 10.1515/hmbci-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Review on role of progestogen (dydrogesterone) in the prevention of gestational hypertension

Abstract: Supplementation of the progestogen, dydrogesterone, in the first trimester to primigravidae has shown great potential in reducing or preventing the incidence of gestational hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Dydrogesterone is a synthetic progestin with enhanced oral bioavailability, known for being highly selective for the progesterone receptor ( Kupferminc et al ., 1990 ; Domitrz et al ., 1999 ). It is effective in treating reproductive disorders such as threatened abortion and recurrent pregnancy loss, and has also been investigated in the prevention of gestational hypertension and preterm birth ( Carp, 2012 ; 2015 ; Hudic et al ., 2016 ; Mohamad Razi et al ., 2016 ). Dydrogesterone has also been described to provide similar reproductive results as vaginal progesterone ( van der Linden et al ., 2015 ; Barbosa et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dydrogesterone is a synthetic progestin with enhanced oral bioavailability, known for being highly selective for the progesterone receptor ( Kupferminc et al ., 1990 ; Domitrz et al ., 1999 ). It is effective in treating reproductive disorders such as threatened abortion and recurrent pregnancy loss, and has also been investigated in the prevention of gestational hypertension and preterm birth ( Carp, 2012 ; 2015 ; Hudic et al ., 2016 ; Mohamad Razi et al ., 2016 ). Dydrogesterone has also been described to provide similar reproductive results as vaginal progesterone ( van der Linden et al ., 2015 ; Barbosa et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gestational hypertension is a complication that specifically occurs in late pregnancy, and includes gestational hypertension, preeclampsia, eclampsia and chronic hypertension ( 1 , 2 ). A clinical investigation suggested that hypertensive disorder is a complication during pregnancy, is a common pregnancy-associated disease and is becoming increasingly present worldwide ( 3 ). However, the etiology of gestational hypertension is yet to be clearly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are a large number of factors that may induce gestational hypertension, and have been found to serve a role in the etiology of these hypertensive disorders, including work stress, depression and anxiety ( 12 , 13 ). Reports also have indicated that angiotensin II type 1 receptor (Ang-IITR), vasodilation converting enzyme (VCE) and α-1A adrenergic receptor (α-ADR) serve crucial roles in the process of gestational hypertension and may be potential targets for the treatment of patients with gestational hypertension in clinical ( 3 , 12 , 13 ). Therefore, a large number of drugs targeting Ang-IITR were introduced and their therapeutic effects for the treatment of gestational hypertension were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In several species, it is recognized that hormonal status can influence systemic blood pressure. In women, Mohamad Razi and Schindler () showed that progesterone decreases systemic blood pressure, thus preventing gestational hypertension. Additionally, Zhao et al.…”
Section: Introductionmentioning
confidence: 99%